Teacher retention in crisis: Informing policy to keep Ghanaian educators in classrooms - Richard Lionel Gorni; Diding Nurdin; Johar Permana; Djaman Satori (Inovasi Kurikulum, 2024)
Ghana's schools face a severe teacher retention crisis, with only 36 percent of teachers in a district survey planning to stay in their roles. Researchers conducted a comprehensive survey of 138 teachers to investigate their reasons for wanting to leave the profession. Common themes emerged, including low pay, poor working conditions, and overwhelming workloads. Additionally, concerns about teacher well-being and the declining status of the teaching profession were highlighted as significant issues. The study sought to identify strategies to keep teachers engaged, employing a theory about employee turnover to guide the analysis. Researchers carefully examined the survey responses and pinpointed key strategies to address the crisis. These included reducing teacher workloads, improving working conditions, and enhancing the prestige and status of the teaching profession. This research provides valuable insights for policymakers seeking effective solutions to Ghana's teacher retention problems. The findings underscore the urgent need to address the factors driving teachers away and implement strategies to maintain a stable, motivated, and highly skilled teaching workforce, which is crucial for advancing Ghana's educational system. AbstrakSekolah-sekolah di Ghana sedang menghadapi krisis retensi guru yang parah, dengan hanya 36 persen guru dalam survei distrik yang berencana untuk tetap menjabat. Peneliti melakukan survei komprehensif terhadap 138 guru untuk mendalami alasan mereka ingin meninggalkan profesinya. Tema-tema umum muncul, termasuk gaji rendah, kondisi kerja yang buruk, dan beban kerja yang sangat berat. Selain itu, kekhawatiran mengenai kesejahteraan guru dan menurunnya status profesi guru juga disoroti sebagai permasalahan yang signifikan. Studi ini berusaha mengidentifikasi strategi untuk menjaga keterlibatan guru, dengan menggunakan teori tentang pergantian karyawan untuk memandu analisis. Melalui pemeriksaan yang cermat terhadap respons survei, para peneliti menunjukkan strategi utama untuk mengatasi krisis ini. Hal ini termasuk mengurangi beban kerja guru, memperbaiki kondisi kerja, dan meningkatkan prestise dan status profesi guru. Penelitian ini memberikan wawasan berharga bagi para pembuat kebijakan yang mencari solusi efektif terhadap masalah retensi guru di Ghana. Temuan-temuan ini menggarisbawahi kebutuhan mendesak untuk mengatasi faktor-faktor yang mendorong guru menjauh dan menerapkan strategi yang dapat mempertahankan tenaga pengajar yang stabil, termotivasi, dan berketerampilan tinggi, yang sangat penting bagi kemajuan sistem pendidikan Ghana.Kata Kunci: pergantian karyawan; pengurangan guru; retensi guru